In-hospital and short-term predictors of mortality in patients with intermediate-high risk pulmonary embolism - Gök, Gülay; Karadağ, Mehmet; Çınar, Tufan; Nurkalem, Zekeriya; Duman, Dursun (Tabriz University of Medical Sciences and Health Services, 2020)
Introduction: The aim of this study was to evaluate the in-hospital and short-term predictive factors of mortality in intermediate-high risk acute pulmonary embolism (PE) patients with right ventricle (RV) dysfunction and myocardial injury.Methods: In this retrospective study, the medical records of 187 patients with a diagnosis of intermediatehigh risk acute PE were evaluated. A contrast-enhanced multi-detector pulmonary angiography was used to confirm diagnosis in all cases. All-cause mortality was determined by obtaining both in-hospital and 30 days follow-up data of patients from medical records.Results: During the in-hospital stay (9.5 +/- 4.72 days), 7 patients died, resulting in an acute PE related in-hospital mortality of 3.2%. Admission heart rate (HR), (Odds ratio (OR), 1.028 95% Confidence interval (CI), 0.002-1.121; P = 0.048) and blood urea nitrogen (BUN) (OR, 1.028 95% CI, 0.002-1.016; P = 0.044) were found to be independent predictors for in-hospital mortality in a multivariate logistic regression analysis. In total, 32 patients (20.9%) died during 30 days follow-up.The presence of congestive heart failure (OR, 0.015, 95%CI, 0.001-0.211; P = 0.002) and dementia (OR, 0.029, 95%CI, 0.002-0.516; P = 0.016) as well as low albumin level (OR, 0.049 95%CI, 0.006-0.383; P = 0.049) were associated with 30 days mortality.Conclusion: HR and BUN were independent predictors of in-hospital mortality and the presence of congestive heart failure, dementia, and low albumin levels were associated with higher 30 days mortality.
Keywords: Acute Pulmonary Embolism; Mortality; Intermediate-High Risk